PROFESSIONAL SELF-CONCEPT OF NURSES AND WILLINGNESS TO REMAIN IN THE PROFESSION - Beta, Gunta; Baļķena, Zane (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The professional self-concept of nurses, who make up the majority of medical practitioners and who participate in the implementation of public health policy, plays an important role in job satisfaction, productivity, which leads to patient satisfaction and development of the profession. Whereas, nurse job satisfaction affects nurse's future plans related to willingness to remain in the profession. Nursing self-concept is shaped and influenced by many different factors, one of them global self-esteem. The aim of the study is to investigate the relationship between the factors forming the professional self-concept, self-esteem and willingness to remain in profession of practicing nurses. The results revealed that there are statistically significant links between some groups of socio-demographic data: age and self-esteem, level of education and self-esteem, as well as the desire to remain in the profession. Statistically significant differences have been identified between respondents' answers according to age group, education level, length of service and certificate in relation to different sub-scales of self-concept.